Peningkatan Kapasitas Dosen dan Mahasiswa dalam Pemanfaatan Software Lisrel di STT Renatus Pematang Siantar - Sihar Tambun (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The purpose of implementing this community service program was to improve the ability of lecturers and students in processing research data using Lisrel software. This activity was carried out through three stages, namely the planning stage, the implementation stage and the evaluation stage. The method used in the implementation of the event is the lecture method and practice. The resource person who became the instructor in this training was a lecturer at the 17 Augustus 1945 Jakarta University as a form of community service. This training was very much needed at STT Renatus Pematang Siantar because there were no lecturers and students who have mastered the use of this software properly. The results of the evaluation were carried out by comparing the pretest and posttest scores. There was an increase in the mastery of software in the majority of the trainees. The majority of participants already understand well how to input data, how to process data and how to interpret the results of data processing. It is hoped that the participants will continue to learn and practice their skills in processing research data with Lisrel software, so that these skills can support the careers of the participants and support the performance of their institutions.